Peningkatan Kemampuan Lompat Jauh menggunakan Model Bermain pada Siswa Tuna Grahita di SLB - Novi Sefriana; Herlin Armisesna (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2021)
This study aims to determine the extent of the improvement in long jump learning using the play model. This research method is carried out by classroom action research (CAR) using two cycles, and each cycle consists of 3 meetings for each process. Each bike is divided into four stages, namely planning, action/observation, reflection, and plan improvement. The results showed that the average value of the initial students was only 30 and was still below the KKM, which was 70. After the action was carried out, the middle-class score increased to 80 at the end of cycle two, and all students achieved scores above the KKM. The conclusion is that using playing models in the form of used bicycle tires and used cardboard can improve fifth-grade mentally disabled students at SLB Negeri Metro in long jump learning. Keywords: Long Jump, Play Model, Mentally Retarded